The Interprocessual-Self Theory in Support of Human Neuroscience Studies - Luis, Elkin O.; Akrivou, Kleio; Bermejo-Martins, Elena; Scalzo, Germán; Orón, José Víctor (Frontiers in Psychology, 2022)
Rather than occurring abstractly (autonomously), ethical growth occurs in interpersonal relationships (IRs). It requires optimally functioning cognitive processes (attention, working memory, episodic/autobiographical memory, inhibition, flexibility, among others), emotional processes (physical contact, motivation, and empathy), processes surrounding ethical, intimacy and identity issues, and other psychological processes (self-knowledge, integration and the capacity for agency). Without intending to be reductionist, we believe that these aspects are essential for optimally engaging in IRs and for personal constitution. While they are all integrated into our daily life, in research and academic work, it is hard to see how they are integrated. Thus, we need better theoretical frameworks for studying them. That study and integration thereof is undertaken differently depending on different views of what it means to live as a human being. With that in mind, this article aims to introduce a new explanatory framework, called the Interprocessual-self (IPS), for the neuroscientific findings that allow for a holistic consideration of the previously mentioned processes. Contributing to knowledge of personal growth and avoiding a reductionist view, we first offer a general description of the research that supports the interrelation between personal virtue in IRs and relevant cognitive, emotional, and ethic-moral processes. This reveals how relationships allow people to relate ethically and grow as persons. We include conceptualizations and descriptions of their neural bases. Secondly, in relation to the IPS model, we explore neuroscientific findings regarding self-knowledge, integration, and agency, all psychological processes that stimulate inner exploration of the self in relation to the other. We find that these fundamental conditions can be understood from IPS theory. Finally, we explore situations that involve the integration of two levels, namely the interpersonal one and the social contexts of relationships